The Fecal Microbiota of Dogs Switching to a Raw Diet Only Partially Converges to That of Wolves - Xu, Jia; Becker, Anne A. M. J.; Luo, Yu; Zhang, Wenfu; Ge, Bingqian; Leng, Chunqing; Wang, Guyue; Ding, Limin; Wang, Jianmei; Fu, Xiaoyu; Janssens, Geert P. J. (Frontiers in Microbiology, 2021)
The genomic signature of dog domestication reveals adaptation to a starch-rich diet compared to their ancestor wolves. Diet is a key element to shape gut microbial populations in a direct way as well as through co-evolution with the host. We investigated the dynamics in the gut microbiota of dogs when shifting from a starch-rich, processed kibble diet to a nature-like raw meat diet, using wolves as a wild reference. Six healthy wolves from a local zoo and six healthy American Staffordshire Terriers were included. Dogs were fed the same commercial kibble diet for at least three months before sampling at day 0 (DC), and then switched to a raw meat diet (the same diet as the wolves) for 28 days. Samples from the dogs were collected at day 1 (DR1), week 1 (DR7), 2 (DR14), 3(DR21), and 4 (DR28). The data showed microbial population of dogs switched from kibble diet to raw diet shifts the gut microbiota closer to that of wolves, yet still showing distinct differences. At phylum level, raw meat consumption increased the relative abundance of Fusobacteria and Bacteroidetes at DR1, DR7, DR14 and DR21 (q<0.05) compared to DC, whereas no differences of these two phyla were observed between DC and DR28. At genus level, Faecalibacterium, Catenbacterium, Allisonella and Megamonas were significantly lower in dogs consuming the raw diet from the first week onwards and in wolves compared to dogs on the kibble diet. Linear discriminant analysis effect size (LEfSe) showed a higher abundance of Stenotrophomonas, Faecalibacterium, Megamonas, Lactobacillus in dogs fed kibble diet compared to dogs fed raw diet for 28 days and wolves. In addition, wolves had greater unidentified Lachnospiraceae compared to dogs irrespective of the diets. These results suggested carbohydrate fermenting bacteria give way to protein fermenters when diet shifted from kibble to raw diet. In conclusion, some microbial phyla, families, genera in dogs showed only temporary change upon dietary shift, whereas some microbial groups moved towards the microbial profile of wolves. These findings open the discussion on the extent of co-evolution of the core microbiota of dogs throughout domestication.